INSTALLATIONS AS THE IMPORTANT FACTOR OF READINESS OF THE FUTURE TEACHERS OF MUSIC TO MUSICAL - EDUCATIONAL ACTIVITY AT SCHOOL. (Pedagogy of Higher and Secondary Education, 2007)
The definite types of the attitudes which promote the perfect level of conduction of musical-educational activities by the future teachers of music are considered in this article.
Keywords: attitude; musical-educational activities; teacher o f music